If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 63 + -3 = n + -5 Combine like terms: 63 + -3 = 60 60 = n + -5 Reorder the terms: 60 = -5 + n Solving 60 = -5 + n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1n' to each side of the equation. 60 + -1n = -5 + n + -1n Combine like terms: n + -1n = 0 60 + -1n = -5 + 0 60 + -1n = -5 Add '-60' to each side of the equation. 60 + -60 + -1n = -5 + -60 Combine like terms: 60 + -60 = 0 0 + -1n = -5 + -60 -1n = -5 + -60 Combine like terms: -5 + -60 = -65 -1n = -65 Divide each side by '-1'. n = 65 Simplifying n = 65
| 2(3r-3)=-22+8r | | -8x+3=14 | | -53-9x=35-5x | | 26=x/-5 | | 4j-3=5j | | 5(-7-6n)=-10-5n | | x^2+4x+8=8x+29 | | 2x=.36 | | 5/9(240) | | 3/7+2/5x=1/5x+1 | | 9h+6=10h | | -28=-x+11-(-5) | | -1/5r=-20 | | 5(t+2)=3.2k | | p^2=3p+28 | | (2x+1)*2+(x+1/2)*2=18 | | 5x+10=30whatisx | | 3x-12+2x=13 | | 11.3-72f=-3.82 | | 2k+k=-9 | | 2k=-9k^2-10 | | 11y-7y-10=73.92 | | -x^2y= | | 3+7x-5=4x-12 | | 5p-12-3(p+8)=4 | | f(-3)=-2(3x-2)+x+9 | | 3-7(-2)-8= | | -7w=42 | | 15x+x=192 | | 20x^3+31x^2+12x=0 | | 5x-3(2x+8)=7 | | 10x+10=6x+26 |